Evaluasi Kesehatan Bank Swasta yang Terdaftar di BEI Periode 2015–2024 - Wanda Alyzza Fitri; Neneng Miskiyah; Agung Anggoro Seto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to evaluate the financial condition of four private banks, namely Bank Mega, Bank JTrust, Bank Danamon, and Bank Panin listed on the Indonesia Stock Exchange during the period 2015 to 2024. The analysis uses the Risk-Based Bank Rating (RBBR) approach with a quantitative method, where the data source is derived from published annual financial statements. The sampling technique was carried out by purposive sampling with the criteria of financial statements available for the last 10 years and the fluctuations in profits in the last three years. The bank's health assessment is carried out through four main aspects. First, the risk profile is measured using non-performing loan (NPL) ratios and liquidity levels through the Loan to Deposit Ratio (LDR). Second, Good Corporate Governance (GCG) is evaluated based on regulatory compliance and transparency reporting. Third, profitability which includes the return on asset ratio (ROA) and net interest margin (Net Interest Margin / NIM). Fourth, the capital aspect is analyzed through the Capital Adequacy Ratio (CAR). The results of the study show that in general, the four banks are in a healthy condition, especially in terms of capital and governance, which reflects the bank's ability to meet the minimum capital requirements and maintain management practices in accordance with banking industry standards. However, significant differences were found in the risk and profitability aspects. Banks that have less than optimal risk management tend to experience an increase in NPLs, while banks that are more efficient in managing operational costs are able to maintain ROA and NIM at a more stable level. In addition, external factors such as global economic conditions, monetary policy, interest rates, and interbank competition also affect financial performance.